Nitrofurantoin and glucose-6-phosphate dehydrogenase deficiency: a safety review. Issue 3 (3rd May 2022) - Recht, Judith; Chansamouth, Vilada; White, Nicholas J.; Ashley, Elizabeth A.
Abstract: Nitrofurantoin, a broad-spectrum antibiotic available since 1953, is used widely for the treatment of urinary tract infections as it often retains activity against drug-resistant uropathogens. It is contraindicated in pregnant women at term, and in neonates. Like trimethoprim/sulfamethoxazole, nitrofurantoin carries a warning for patients with known sensitivity to oxidant drugs, notably glucose-6-phosphate dehydrogenase (G6PD) deficiency, in whom it may cause haemolytic anaemia. This is a barrier to uptake in tropical regions where there is a high burden of antimicrobial resistance and where G6PD deficiency is common. Early studies of erythrocyte survival following nitrofurantoin suggest it is less likely to cause oxidant haemolysis in individuals with G6PD deficiency than primaquine. Here we review reports of haemolysis associated with nitrofurantoin from the published literature and from USA (FDA Adverse Event Reporting System; FAERS) and European (VigiBase) pharmacovigilance databases. In total, 318 episodes of haemolytic anaemia were reported and 10 deaths, with 42 (13%) in individuals with confirmed or highly probable G6PD deficiency, out of at least 245 million exposures. A causal link between death and exposure was not reported and a precise risk estimation in G6PD-deficient individuals was not possible as there are few reports from regions where this enzymopathy is most prevalent. The evidence suggests a total daily dose of 200 mg nitrofurantoin may be used for short (3–5 day) course urinary tract infection treatment without G6PD screening when accompanied by appropriate advice. Pharmacovigilance in countries with high prevalence of G6PD-deficiency is recommended to monitor for serious adverse events.